Mucormycosis in South America: A review of 143 reported cases. Issue 9 (11th July 2019) - Nucci, Marcio; Engelhardt, Marc; Hamed, Kamal
Summary: Mucormycosis is a rare but important invasive fungal disease that most often affects immunocompromised hosts. The incidence of mucormycosis appears to be increasing worldwide, as risk factors such as the use of immunosuppressive therapies become more common. We report the results of a literature review of 143 mucormycosis cases reported in South America between 1960 and 2018. The number of reported cases has increased by decade, from 6 in the 1960s to 51 in the 2010s. The most common underlying conditions associated with mucormycosis in South America were diabetes mellitus (42.0%) and penetrating trauma/burns (20.0%). Underlying conditions involving immunosuppression, including treatment of haematologic malignancy, solid organ transplant, and corticosteroid use, also accounted for a large proportion of cases (45.5%). Between 1960 and 2018, cases of mucormycosis associated with conditions involving immunosuppression accounted for the highest mortality rate (58.5%), followed by diabetes mellitus (45.0%), and penetrating trauma/burns (37.9%). Overall mortality decreased from 100% to 39.4% during this period, mainly driven by the increasing availability and use of antifungal therapies and surgical intervention. However, these treatments are not yet universally utilised across the region in the treatment of mucormycosis; efforts to improve availability of effective treatments would be likely to improve outcomes.